Infection risk among adults with down syndrome: a two group series of 101 patients in a tertiary center - Guffroy, Aurélien; Dieudonné, Yannick; Uring-Lambert, Beatrice; Goetz, Joelle; Alembik, Yves; Korganow, Anne-Sophie (Orphanet journal of rare diseases, 2019)
Down syndrome (DS) is the most common form of viable chromosomal abnormality. DS is associated with recurrent infections, auto-immunity and malignancies in children. Little is known about immunity and infections in DS at adulthood. We studied two separate group of adults (> 18 years old) with DS in a single referral tertiary center (Strasbourg University Hospital). The first group included 37 ambulatory DS patients between November 2014 and May 2017. We analyzed exhaustive serological and immunobiological parameters, at one point, together with the prevalence of infections, autoimmune manifestations and malignancies. The second group included 64 hospitalized patients (138 stays) in the same center, between January 2005 and December 2016. One hundred and one adult patients with DS were included. Unlike children and despite a global lymphopenia, adults with DS underwent few infections in our ambulatory group. They did not experience any malignancy and, apart from hypothyroidism, they presented only occasional autoimmune manifestations. Hospitalized DS patients were older than ambulatory ones (median age 47 years (18-73) vs. 27 (18-52), p < 0.0001) and admitted mostly for infections (76.8%). Infections were associated with epilepsy and dementia (OR 6.5 (2.2-19), p = 0.001; p = 0.0006 in multivariate analysis) and higher mortality (OR 7.4 (1.4-37), p = 0.01). Despite persistent immunobiological abnormalities at adulthood, young ambulatory adults with DS remain healthy with a low rate of infections. Infections are associated with neurological degeneration and increase the mortality arguing for a dedicated support of older DS patients. ClinicalTrials.gov: NCT01663675 (August 13, 2012). Hospital Clinical Research Program (PHRC): number 2012-A00466-37 (Dr Y. Alembik).